Prevalence and Predictors of Harmful Khat Use among University Students in Ethiopia - Ewenat Gebrehanna; Yemane Berhane; Alemayehu Worku (SAGE Publishing, 2014)
Comprehensive assessment of harmful khat use is lacking because often researchers rely on a simple tool for studying it. The aim of this study was to determine the prevalence and predictors of harmful khat use among Ethiopian university students by developing a comprehensive scale based on Alcohol Use Identification Test, Severity of Dependency Syndrome scale, and International Classification of Diseases definition of harmful substance use. Logistic regression was performed to identify predictors of harmful khat use. One in five current khat user students were identified as harmful khat users [20.6% (95% CI: 14.3-22.3)]. Harmful khat use in this study was strongly associated with chewing at commercial places [adjusted odds ratio (AOR) = 2.32 (95% CI: 1.01-5.33)], and having non-student friends accompanying the khat-chewing ceremony [AOR = 3.77 (95% CI: 1.09-13.03). Students who started chewing khat at the age of 20 years or later [AOR = 0.19 (95% CI: 0.07-0.55)] and those who preferred to study in the library [AOR = 0.31(95% CI: 0.12-0.81)] were less likely to be harmful khat users. The university authorities, in addition to provision of student guidance on substance-use prevention, need to work in collaboration with the surrounding community and responsible public authorities in order to reduce harmful use of khat by their students.